Photoluminescence features of AgBr nanoparticles formed in porous glass matrices - Doycho, Igor K.; Gevelyuk, Sergiy A.; Ptashchenko, Olexandr O.; Rysiakiewicz-Pasek, Ewa; Tolmachova, Tetiana M.; Tyurin, Olexandr V.; Zhukov, Sergiy O. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The photoluminescence of AgBr nanoparticles formed by a two stage liquid-gas microsynthesis technology in two types of porous glass with different sizes of pores was investigated. Polyvinyl alcohol (Polinol) was used as a binder. It has been found that AgBr nanoparticles in the glasses with smaller pores luminesce more intensively, and we attribute this phenomenon to the differ-ences in pore size distributions. The luminescence spectra were shown to have two maxima corresponding to AgBr nanoparticles formed within the nanopores of two different sizes characteristic of each of the matrices. In both cases, the spectra excited by xenon lamp irradiation are more intensive than those stimulated by a 337-nm nitrogen laser. Comparing the maxima shifts in the phosphorescence excitation spectra with ones in phosphorescence spectra we can conclude that the luminescence and phosphorescence centers in AgBr nanoparticles are of identical nature in the matrices of both types. The investigation results fit neatly into the inherently consistent quantum confinement model and are well correlated with the poroscopic spectra of both types of glass.
Optica Applicata, Vol. 40, 2010, nr 2, s. 323-332
Keywords: optyka; porous glasses; silver bromide; nanoparticles; luminescence properties; quantum confinement